Rfid Based Exam Paper Leakage Protection System - et. al., Keerthan K S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The soul of the society is Education as it passes from one generation to another. However today, when we read news articles, we realize that, This has been corrupted by question paper leakage.. We propose an electronic protection in order to prevent exam paper leakage. Question papers will be stored and sent to the examination centres in a sealed electronic box. The device will ask for the main examiner to scan his RFID tag. Then the box lock is open .And invigilator must scan his card to print question paper and distributed to the exam candidates . This will enable the papers to be locked and sealed till the point in time when the papers need to be brought out for the distribution to the students in the examination hall.